Plant photoreceptors and their signaling components compete for COP1 binding via VP peptide motifs. (15th July 2019) - Lau, Kelvin; Podolec, Roman; Chappuis, Richard; Ulm, Roman; Hothorn, Michael
Abstract: Plants sense different parts of the sun's light spectrum using distinct photoreceptors, which signal through the E3 ubiquitin ligase COP1. Here, we analyze why many COP1‐interacting transcription factors and photoreceptors harbor sequence‐divergent Val‐Pro (VP) motifs that bind COP1 with different binding affinities. Crystal structures of the VP motifs of the UV‐B photoreceptor UVR8 and the transcription factor HY5 in complex with COP1, quantitative binding assays, and reverse genetic experiments together suggest that UVR8 and HY5 compete for COP1. Photoactivation of UVR8 leads to high‐affinity cooperative binding of its VP motif and its photosensing core to COP1, preventing COP1 binding to its substrate HY5. UVR8–VP motif chimeras suggest that UV‐B signaling specificity resides in the UVR8 photoreceptor core. Different COP1–VP peptide motif complexes highlight sequence fingerprints required for COP1 targeting. The blue‐light photoreceptors CRY1 and CRY2 also compete with transcription factors for COP1 binding using similar VP motifs. Thus, our work reveals that different photoreceptors and their signaling components compete for COP1 via a conserved mechanism to control different light signaling cascades. Synopsis: Light‐activated plant photoreceptors bind and inhibit the E3 ubiquitin ligase COP1, thus protecting downstream transcription factors from degradation. X‐ray structures, quantitative binding assays and reverse genetics show that photoreceptors and transcription factors compete for COP1 binding via Val‐Pro (VP) motifs. COP1 binds to VP motifs of photoreceptors (e.g. UVR8, CRY1 and CRY2) and downstream transcription factors, such as HY5, HFR1 and CO. COP1 binds more strongly to its targets HY5 and CO than to the corresponding photoreceptors UVR8 and CRY2 in the absence of light stimulation. UV‐B‐activated UVR8 exhibits high‐affinity, cooperative binding to COP1, allowing it to displace HY5 from COP1. Light activation also increases CRY2 affinity towards COP1, suggesting a common regulatory mechanism. Abstract : Light activation increases affinity of various photoreceptors for the E3 ligase COP1, resulting in protection of light‐regulated transcription factors from COP1‐mediated degradation.